Anti - swing control strategy for automatic 3 dof crane system using FLC - Ruslee, Ruslinda (2008)
The 3 Degree-of-Freedom (DOF) crane represents one of the most widely deployed real-world platforms in the world today. It uses levers and pulleys for gripping, lifting and moving loads horizontally, as well as lowering and releasing the gripper to the original position. Hence the system produces swing angle which need to be controlled so that the payload could be transferred efficiently. The existing 3 DOF systems used conventional Linear Quadratic Regulator (LQR) controller to control the position and swing angle. This project report proposed the usage of Fuzzy Logic Controller (FLC) in place ofLQR controller. FLC has a simpler and practical design approached. It avoids laborious mathematical formulation and computation thus reducing operating time. The FLC performance for position control and anti-swing control are compared with LQR controller using MA TLAB simulation. The simulation results showed, under laboratory limitation, that FLC performed better compared to the conventional LQR controller.